Dinamika Interaksi Edukatif Dalam Meningkatkan Hasil Belajar Siswa Mata Pelajaran Sejarah Kebudayaan Islam Di MIS TPI Al Fajar Deli Serdang - Syahri Maulina Tarigan; Alimuddin Siregar; Hotni Sari Harahap (Journal of Innovative and Creativity, 2025)
The research that has been conducted is titled "The Dynamics of Educational Interaction in Improving Student Learning Outcomes in Islamic Cultural History Subjects at MIS TPI Al Fajar." This is based on student learning outcomes in Islamic Cultural History subjects. The dynamics of educational interaction is what happens within the learning process. The purpose of this research is to understand the dynamics of educational interaction that occurs in improving students' learning outcomes in Islamic Cultural History. This type of research is qualitative research with a descriptive approach. The data collection methods are observation, interviews, and documentation. Data analysis techniques include data reduction, data presentation, and drawing conclusions. As for the data sources for the research informants, they are the School Principal, the Islamic Cultural History subject teachers, and representatives from several 6th-grade students. The research findings indicate that the dynamics of educational interaction between teachers and students are quite good. In the learning process, the Islamic Cultural History teacher uses lecture and question-and-answer methods. However, not all students can focus and listen to the teacher well, and not all students are able to understand or answer the teacher's questions effectively. This results in a less active learning environment. In this case, the teacher communicates in a two-way manner, and the factors hindering the dynamics of educational interaction in improving student learning outcomes are the school's guidebooks, which are in the form of student worksheets, and the absence of storybooks prepared by the school as an addition to teaching and learning activities in Islamic Cultural History.